ANALISIS KELAYAKAN DAN KESESUAIAN DESA CANDIREJO DAN LOPAIT MENJADI DESA AGROWISATA - Yosua Aprianto Kasim; Alfred Jansen Sutrisno (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
Tuntang District is located in Semarang Regency, Central Java Province. This district has an aquatic landscape, namely Rawa Pening Lake. Rawa Pening Lake has attractive natural tourism potential because of its very beautiful natural scenery and Rawa Pening Lake is sorrounded by mountains. In addition, the lake area is also used as a place for fish cultivation because the outskirts have fish cages, and are also used for irrigation of rice fields. However, this potential has not been developed properly. So the purpose of this research is to analyze the suitability and feasibility of Candirejo Village and Lopait Village to become agro-tourism villages. The research method used is to identify land use using a classification method based on the condition of satellite imagery, Analyzing the social conditions (perceptions) of the community, where the sample was selected using the stratified random sampling method, Analyzing the visual conditions (landscape aesthetics) using the Scenic Beauty Estimation (SBE) method, and Assessing the feasibility and suitability of each village based on the results of the previous three stages. The results of the study can be seen in the table of the total value of all the variables in the 2 agro-tourism villages. In conclusion, Candirejo Village and Lopait Village have the potential to be used as agro-tourism villages, but Lopait Village still needs to be improved in several variables.